Locus of Control and Self Efficacy on Entrepreneurial Intentions in Vocational High School Students - Viguna, Ayu Imelda; Indriayu, Mintasih; Noviani, Leny (Universitas Pendidikan Ganesha, 2025)
Many vocational high school graduates face difficulties in finding jobs. This has an impact on unemployed graduates. Based on this, this study aims to analyze the effect of locus of control and self eficacy on the intensity of entrepreneurship of vocational high school students majoring in business management. This type of research is quantitative research. The population in this study was 114 students. The sample of this study was 73 students using the proportional random sampling method. The methods used in collecting data were questionnaires and documentation. The research instrument was a questionnaire. The technique used in analyzing the data was inferential statistical analysis. The study results showed that first, there was a positive and significant relationship between locus of control and the intensity of entrepreneurship in vocational high school students in Pringsewu. This means that when students have a strong locus of control, their intensity for entrepreneurship tends to be high. Conversely, if the locus of control is low, the intensity of entrepreneurship also tends to be low. Second, there is a positive and significant influence between self-efficacy and the intensity of entrepreneurship in vocational high school students in Pringsewu. It was concluded that high levels of self-efficacy in students were related to high intentions to become entrepreneurs.